Smart contracts based on multi-agent negotiation - Barbosa, Ricardo (2021)
Decision-making processes and collaboration scenarios expect users to trust the negotiation process and respective fulfilment of its outcomes. Agents inherit the preferences of the entities that they represent and can engage in negotiation processes to fulfil their goals, or the objectives of a group. When faced with the challenges of multi-agent systems and group decision-making processes and negotiation, the traditional solutions to trust issues are supported by an inclusion of a third-party entity that, consequently, raises new trust challenges. In this work, we propose an alternative solution to this problem, based on a combination of Smart Contracts and blockchain. The immutable and distributed characteristics of these technologies provide a trustworthy support for the negotiation process, including knowledge representation. Additionally, by focusing on the terms used during the negotiation, we can improve Smart Contracts through the automatization of their contractual terms, where their parameters are derived from the output of the negotiation process between agents. This mainly reinforces that negotiation can benefit from the inclusion of Smart Contracts, and vice versa. The proposed model should be independent of protocol, language, and decision processes, however special attention should be addressed to communication, namely to the simplification and generalization of locutions.